Diabetes management training for female community health volunteers in Western Nepal: an implementation experience - Bishal Gyawali; Shiva Raj Mishra; Dinesh Neupane; Abhinav Vaidya; Annelli Sandbæk; Per Kallestrup (BMC, 2018)
Abstract Background In the backdroup of a rapidly increasing burden of diabetes in Nepal, a community-based diabetes management program is implemented involving female community health volunteers (FCHVs) under the government run FCHVs program. FCHVs received an intensive one-week training workshop on prevention, control and management of diabetes. The training program was implemented and evaluated to enhance diabetes knowledge of FCHVs and matched according to their literacy level. Methods A range of teaching methods were applied, including desk review, active participation, lectures, presentations, discussions, role plays, demonstration and field test. Evaluation of the knowledge attained was done by testing before and after the workshop. Major milestones in the development of the training module were presented from desk review and ending in stakeholder's participation in reviewing and revising the training package. The qualitative interview transcripts of FCHVs were analyzed thematically. Results A 5-day training package was developed through a desk review of interventions using community health workers (CHWs) on diabetes management from similar settings. Training module included home-based blood glucose monitoring and home-based health education on life style counselling delivered through a participatory learning approach. There were 20 participants with a mean age of 47 years (SD ± 5.7). The overall assessment of knowledge of diabetes before-after the training, evaluated by the Diabetes Knowledge Questionnaire (DKQ) showed increases in mean score from 40.4% before training to a mean score of 63.3% after training (Paired t-test: t = − 11.1, P < 0.001, and Wilcoxon test for paired samples: z = − 3.930, P = 0.0001). Focus group discussions (FGDs) revealed that FCHVs had a favorable perception of the training program's effectiveness. Conclusions If FCHVs are appropriately trained they may be instrumental in providing counseling and screening for diabetes management in their communities.